An approach to the didactic treatment of Physics linked with mathematics (Revisión) (REDEL. Revista Granmense de Desarrollo Local, 2021)
An observation of the interdisciplinary become a structural foundation for a pertinent didactic treatment of the knowledge about the existence of the objects, processes, phenomena and relations among themselves. Based in the above, a revision of some tendencies is accomplished, like approximation to the conception of the didactic treatment of the particular knowledge. Specifically, the mathematical modeling applies to Physics, highlighting the importance of the integrative learning.
Keywords: interdisciplinary; didactic; mathematics; physics